The Influence of School Culture and School Quality on Teachers’ Performance through Achievement Motivation of Vocational High School Teachers in Bangsri District, Jepara Regency - Dwi Agung Suhartono; Tri Joko Raharjo (Educational Management, 2025)
Teachers’ performance is the outcome of their competence, responsibility, and dedication in accomplishing educational goals. Various factors may influence teachers’ performance, including school culture, school quality, and achievement motivation. The objective of this research was to analyze the influence of school culture and school quality on teachers’ performance through achievement motivation as an intervening variable among vocational high school teachers in Bangsri District, Jepara Regency. A quantitative descriptive approach was employed for this study. The population consisted of 129 teachers from both public and private vocational high schools in Bangsri District, Jepara Regency. The sampling technique used was total sampling. Data were collected through a questionnaire that had been tested for validity and reliability. Path analysis was applied to test the hypothesis using SPSS version 23. The findings revealed that school culture and school quality have a direct, positive, and significant influence on achievement motivation and teachers’ performance. Moreover, both variables also have indirect effects on teachers’ performance through achievement motivation. Based on these results, it can be concluded that school culture and school quality strongly affect teachers’ performance both directly and indirectly through achievement motivation. Therefore, fostering a positive school culture and improving school quality continuously are essential to enhance teachers’ motivation and performance in achieving educational excellence.